Makna Kadhib dalam QS. Ali Imran [3]: 94 Perspektif Tafsir Fath al-Qadir Karya al-Shawkani - Nur Falah, Muhammad Zulfikar; an-Najaa, Sarah Safinah (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2024)
AbstractThis article explicitly reveals the meaning of "kadhib" in QS. A<li Imra>n [3]: 94 from the perspective of the Fath al-Qadir interpretation. This is based on the background that the term regarding lying is an interesting discussion, fundamentally conducted for hidden purposes that can only be known by the individual themselves. This research employs a descriptive analytical method through literature review with relevant and credible sources such as books, journals, theses, and others. Before exploring the content of the Quran, the author discusses the biography of al-Shawkani and the profile of his tafsir book. The results of this study indicate that the context of QS. A<li Imra>n [3]: 94, according to the Fath al-Qadir interpretation, is actualized in relation to the characteristics of the Jewish people. Although not specifically explained, al-Shawkani interprets the word "kadhib" in QS. A<li Imra>n [3]: 94 as a lie committed intentionally, and the implications of his statement lean more towards an element of inconsistency with the essence behind reality.Keywords: Kadhib; QS. A<li Imra>n [3]: 94; Tafsir Fath} al-Qadi>r. AbstrakArtikel ini mengungkap secara eksplisit tentang makna kadhib dalam QS. A<li Imra>n [3]: 94 perspektif tafsir Fath} al-Qadi>r. Hal ini diambil melalui latar belakang bahwa terma perihal berbohong menjadi salah satu pembahasan menarik, yang pada dasarnya dilakukan atas dasar tujuan tersembunyi dan tidak dapat diketahui selain dirinya sendiri. Penelitian ini menggunakan metode deskriptif analisis melalui penelusuran pustaka dengan sumber yang relevan dan kredibel seperti buku, jurnal, skripsi, dan lainnya. Sebelum mengeksplorasi isi Al-Qur'an, penulis membahas biografi al-Shawkani dan profil kitab tafsirnya. Hasil penelitian ini adalah konteks pada QS. A<li Imra>n [3]: 94, menurut tafsir Fath} al-Qadi>r, diaktualisasikan kepada sifat kaum Yahudi. Meskipun tidak dijelaskan secara spesifik, al-Shawkani memaknai kata kadhib dalam QS. A<li Imra>n [3]: 94 dengan kebohongan yang dilakukan secara sengaja dan implikasi pernyataannya lebih mengarah kepada unsur ketidaksesuaian terhadap hakikat dibalik realitas. Kata Kunci: Kadhib; QS. A<li Imra>n [3]: 94; Tafsir Fath} al-Qadi>r.